Diagnostic Process for Autism Spectrum Disorder: A Meta-Analysis of Worldwide Clinical Practice Guidelines for the Initial Somatic Assessment - Tom Dauchez; Guillaume Camelot; Charlotte Levy; Toky Rajerison; Kellen Briot; Adrien Pizano; Marie-Maude Geoffray; Loic Landrieu; Manuel Bouvard; Anouck Amestoy (MDPI AG, 2022)
(1) Background: Autism spectrum disorder (ASD) is a neurodevelopmental disorder that is highly associated with various somatic conditions that can be masked by the core symptoms of ASD and thus complicate the diagnosis. Identifying co-occurring somatic disorders is critical for providing effective healthcare and social services for ASD populations and influences their long-term outcomes. A systematic assessment of co-occurring somatic conditions is essential during this ASD diagnostic process. Therefore, this study aimed to identify the organization and content of the initial somatic assessment (ISA). (2) Methods: We conducted a systematic review of the clinical practice guidelines (CPG) for the ASD diagnostic process published between January 2005 and December 2019 in English and French and performed an appraisal following the Appraisal of Guidelines Research and Evaluation, second edition (AGREE-II). (3) Results: We selected 14 CPGs that were heterogeneous in quality, with methodological scores between 32.3 and 91.9. Clinical examinations are the first step in the ISA, and the participation of pediatric, neuropediatric, and genetic specialists was highly recommended by the majority of the CPGs. The recommendations included hearing screening tests (10/14), visual examinations (8/14), and systematic genetic investigations (4/14). The CPGs also described additional investigations that should be conducted based on numerous warning signs. (4) Conclusions: Screening for consensual international warning signs is necessary to perform a comprehensive and systematic ISA during the ASD diagnostic process. A "referral form" could be used to guide clinicians and improve the coordination process. This tool may reinforce epidemiological data on co-occurring somatic disorders in patients with ASD.